As written, you have

3^2 - 10/4^2 - 12

= 9 - (10/16) - 12 (exponents are evaluated first, then division)

= 8 6/16 - 12 (addition and subtraction are next, left to right)

= -3 10/16

= -3 5/8 (here, we reduce the fraction)

If you intend parentheses, the result is different.

(3^2 - 10)/(4^2 - 12)

= (9-10)/(16-12) (exponents)

= -1/4 (then subtraction)

3^2 - 10/4^2 - 12

= 9 - (10/16) - 12 (exponents are evaluated first, then division)

= 8 6/16 - 12 (addition and subtraction are next, left to right)

= -3 10/16

= -3 5/8 (here, we reduce the fraction)

If you intend parentheses, the result is different.

(3^2 - 10)/(4^2 - 12)

= (9-10)/(16-12) (exponents)

= -1/4 (then subtraction)